KRONİK HEPATİT VE SİROZ TANILI HASTALARDA HEPATİT E VİRÜS ENFEKSİYONUNUN SIKLIĞI - KAYALI, SÜMEYRA (Fırat Üniveristesi, 2021)
Hepatit E virüsü; Hepeviridae ailesinin Hepevirus cinsinde yer alan RNA virüsüdür. Hepatit E virüs enfeksiyonu klinik olarak genellikle çocuklarda asemptomatik, erişkin yaş grubunda ise semptomatik seyreder. İyi pişmemiş enfekte hayvanların etlerinin tüketilmesi ve kan transfüzyonu ile bulaşabilse de temel bulaş yolu fekal-oral yoldur. Kronik hepatit ve siroz tanılı hastalarda hepatit E enfeksiyonu akut alevlenmeler, akut karaciğer hasarı, dekompansasyon ve ölüm gibi kötü sonuçlara neden olmaktadır. Hepatit E enfeksiyonu varlığını araştırmak için; 30 otoimmün hepatit, 30 siroz ve 40 kronik HBV tanılı hasta çalışmaya dahil edildi. Bu hastalardan elde edilen serum örneklerinde mikro ELISA ile anti HEV IgM ve anti HEV IgG, RT-PCR ile HEV RNA araştırıldı. Otoimmün hepatit grubunda %13 oranında anti HEV IgM ve anti HEV IgG pozitifliği görüldü. Siroz grubunda %33 anti HEV IgM, %50 anti HEV IgG pozitifliği görüldü. Kronik HBV grubunda ise %7,5 anti HEV IgM, %17,5 anti HEV IgG pozitifliği görüldü. Her üç hasta grubunda da beklenenden yüksek HEV seropozitifliği saptandı. Hastaların hiçbirinde HEV RNA saptanamadı. Kronik hepatit ve siroz tanılı hastalarda klinik yaklaşımlarda HEV enfeksiyonu göz ardı edilmemeli ve HEV bulaşının önüne geçilmesi için hastaların temiz içme suyu ve iyi pişmiş et tüketimi açısından bilinçlendirilmesi gerekmektedir. Anahtar kelime: Hepatit E virüsü, Siroz, Kronik hepatit, Hepatit B virüsü, Otoimmün hepatit

Hepatitis E virus; it is an RNA virus located in the Hepevirus genus of the Hepeviridae family. Hepatitis E virus infection is clinically usually asymptomatic in children and symptomatic in the adult age group. Although consumption of the meat of infected animals that are not cooked well can be transmitted by blood transfusion, the main transmission route is the fecal-oral route. Hepatitis E infection causes adverse outcomes such as acute exacerbations, acute liver damage, decompensation and death in patients diagnosed with chronic hepatitis and cirrhosis. To investigate the presence of hepatitis E infection; 30 autoimmune hepatitis, 30 cirrhosis and 40 chronic HBV patients were included in the study. Anti HEV IgM and anti HEV IgG were investigated by micro ELISA and HEV RNA by RT-PCR in serum samples obtained from these patients. In the autoimmune hepatitis group, anti HEV IgM and anti HEV IgG positivity was observed with a rate of 13%. In the cirrhosis group, 33% anti HEV IgM and 50% anti HEV IgG positivity were observed. In the chronic HBV group, 7.5% anti HEV IgM and 17.5% anti HEV IgG positivity were observed. HEV seropositivity was higher than expected in all three patient groups. HEV RNA could not be detected in any of the patients. HEV infection should not be ignored in clinical approaches in patients diagnosed with chronic hepatitis and cirrhosis, and patients should be informed about clean drinking water and well-cooked meat consumption in order to prevent HEV transmission. Keywords: Hepatitis E virus, Cirrhosis, Chronic hepatitis, Hepatitis B virus, Autoimmune hepatitis
The frequency of hepatitis E infection in patients diagnosed with chronic hepatitis and cirrhosis
Keywords: Mikrobiyoloji